2015
DOI: 10.1210/jc.2014-4053
|View full text |Cite
|
Sign up to set email alerts
|

High Diagnostic Accuracy Based onCLDN10,HMGA2, andLAMB3Transcripts in Papillary Thyroid Carcinoma

Abstract: A promising tool with high performance for PTC diagnosis based on three transcripts was designed with the potential to predict lymph node metastasis risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…Chiappetta et al reported that the mRNA expression of HMGA2 is associated with malignant phenotype in human thyroid neoplasias [44]. HMGA2 was also used as a diagnostic marker in previous studies [14, 45]. In our study, HMGA2 was significantly upregulated in primary TC tissue, compared with benign and normal thyroid nodules.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Chiappetta et al reported that the mRNA expression of HMGA2 is associated with malignant phenotype in human thyroid neoplasias [44]. HMGA2 was also used as a diagnostic marker in previous studies [14, 45]. In our study, HMGA2 was significantly upregulated in primary TC tissue, compared with benign and normal thyroid nodules.…”
Section: Discussionsupporting
confidence: 64%
“…Another panel, named ThyroSeq v2 assay, which consists of more than 50 gene mutations and gene fusions (more than 1,000 hotspots), performed with 90 % sensitivity, 93 % specificity, 83 % PPV, and 96 % NPV by using next-generation sequence [8]. Other studies also achieved encouraging effects [1419]. However, these diagnostic panels are too complex and costly to apply in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that HMGA2 is overexpressed in PTC and can be used as a biomarker for distinguish- ing benign from malignant thyroid tumors. 14,15,22,25,27 The KEEG pathway analysis in this study showed that HMGA2 was enriched in the pathway of "transcriptional misregulation in cancer" .The correlation coefficient between HIT000218960 and HMGA2 was 0.999083. In addition, qRT-PCR results indicated that HIT000218960 was significantly upregulated in PTC tissues compared with noncancerous thyroid tissues, which was consistent with microarray data ( Fig.…”
Section: Identification Of Lncrna-hit000218960 Potentially Associatedmentioning
confidence: 62%
“…The reported studies on the association between HMGA2 and clinicopathological features mostly focused on the diagnostic utility of HMGA2 to distinguish between benign and malignant thyroid tumors. [21][22][23][24][25][26] In other malignancies, such as nasopharyngeal carcinoma, high HMGA2 expression is correlated with N stage, 2-year metastasis status and poor survival prognosis. 27,28 The correlation between HIT000218960 expression and clinicopathological features observed in our study was consistent with that of HMGA2.…”
Section: Discussionmentioning
confidence: 99%